Media serbołużyckie jako media lokalne = Sorbian media as the local media - Mieczkowska, Małgorzata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Sorbian media may be treated as a kind of local media due to several factors. Among them are environmentalism, thematic profile (referring to a particular area - Lusatia) and the limited public conditioned by the size of Sorbian community. Relying on specific areas of interest connected with the local environment and a small circle of distribution enable a direct contact of the public with events reported by the media.
Keywords: media; media lokalne; Serbowie Łużyccy